Predictable increase in female reproductive window: A simple model connecting age of reproduction, menopause, and longevity - Innan, Hideki; Vaiman, Daniel; Veitia, Reiner A. (BioEssays, 2021)
With the ever‐increasing lifespan along with societal changes, women can marry and procreate later than in previous centuries. However, pathogenic genetic variants segregating in the population can lead to female subfertility or infertility well before the average age of normal menopause, leading to counter‐selection of such deleterious alleles. In reviewing this field, we speculate that a logical consequence would be the later occurrence of menopause and the extension of women's reproductive lifespan. We illustrate this point with a simple model that applies to other variants that contribute to female infertility, including epigenetic variation. We also consider the effect of medical interventions and lifestyle. Pathogenic genetic variants segregating in the population can lead to female subfertility or infertility well before the average age of normal menopause, leading to counter‐selection of such deleterious alleles. As women marry later than in previous centuries, we speculate that a logical consequence would be the later occurrence of menopause and the extension of their reproductive window.